Pengaruh Supporting Electrolyte terhadap Deteksi Ion Logam Pb(II) dan Cu(II) menggunakan PLE Termodifikasi Lapisan Tipis Perak dengan Metode Voltammetri - Sisri Wartati; Trisna Kumala Sari (MASALIQ, 2025)
This study aims to evaluate the effect of different supporting electrolytes on the detection sensitivity of Pb(II) and Cu(II) ions simultaneously using a Pencil Lead Electrode (PLE) modified with a thin silver layer via electrodeposition. The modification was carried out using a 5 mM AgNO₃ solution in 0.1 M KNO₃ through cyclic voltammetry, producing reduction and oxidation peaks at +0.2256 V and +0.5253 V, respectively, indicating successful silver deposition on the electrode surface. The supporting electrolyte variations included 0.1 M solutions of HNO₃, H₂SO₄, and HClO₄, tested for 1 mM Pb(II) and Cu(II) ion analysis. The voltammogram results showed that 0.1 M HNO₃ yielded the highest current responses 1.3550 mA for Pb(II) and 1.3305 mA for Cu(II) making it the most optimal supporting electrolyte. These differences are attributed to the ionic mobility and diffusion rate of the species toward the electrode surface. The findings demonstrate that the choice of supporting electrolyte significantly influences the performance of electrochemical sensors. This research contributes to the development of efficient, cost-effective, and sensitive PLE-based sensors for simultaneous heavy metal detection.